The State of the Criminology of Crimes of the State - Rothe, Dawn (Social justice, 2006)
Part of a special issue on immigration rights and national insecurity. The writers explore the origins of a criminology of crimes of the state. They survey the present condition of the criminology of crimes of the state and identify a potential agenda to advance this somewhat marginalized criminological enterprise. They examine the interrelationship of a criminology of crimes of the state with cognate areas of criminological inquiry and explore some of the core sources of resistance to, recognition of, and engagement with such an endeavor within the field of criminology. In conclusion, they propose an agenda for a criminology for crimes of the state.